General Frame of Reference: Language, Literature, Objectives of Education - Tamil I (with Glossary) - (:unkn) unknown (My University, 2002)
The academic resources provided in these five volumes put together, will serve as a perennial source to all those associated with language and literature education for obtaining adequate information. Accordingly, teachers will have a lot of graded resources for appropriate lesson planning with clearly demarcated components of language and literature, and the behavioural traits of personality both at the macro and micro levels.
Keywords: Tamil; English